2019
DOI: 10.1177/2054358119830700
|View full text |Cite
|
Sign up to set email alerts
|

A Survey Study of Self-Rated Patients’ Knowledge About AKI in a Post-Discharge AKI Clinic

Abstract: Background: Survivors of acute kidney injury (AKI) are at risk of adverse outcomes. Post-discharge nephrology care may improve patients’ AKI knowledge and prevent post-AKI complications. Objective: The purpose of this study was to examine patients’ awareness about their AKI diagnosis and self-rated knowledge and severity of AKI before and after their first post-discharge AKI Clinic encounter. Design: We conducted a pre- and post-survey study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
0
20
1
Order By: Relevance
“…Considering the high incidence of AKI and improvements in short-term survival (74), these long-term sequelae of AKI present a major unmet clinical need, with no proven interventions or data to inform optimal care provision. Patients often receive no follow-up after hospital discharge (16), and they often do not realize that they have had AKI (71,75). The evidence base describing the long-term sequelae of AKI continues to grow, adding to our understanding and increasing awareness of these issues.…”
Section: Conclusion and Areas Of Uncertaintymentioning
confidence: 99%
“…Considering the high incidence of AKI and improvements in short-term survival (74), these long-term sequelae of AKI present a major unmet clinical need, with no proven interventions or data to inform optimal care provision. Patients often receive no follow-up after hospital discharge (16), and they often do not realize that they have had AKI (71,75). The evidence base describing the long-term sequelae of AKI continues to grow, adding to our understanding and increasing awareness of these issues.…”
Section: Conclusion and Areas Of Uncertaintymentioning
confidence: 99%
“… 12 , 19 , 20 There is mounting evidence that tailored postdischarge AKI clinics serve an important role in improving AKI knowledge and self-management behaviors. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] There is mounting evidence that J o u r n a l P r e -p r o o f tailored post-discharge AKI clinics serve an important role in improving AKI knowledge and self-management behaviors. 22,23 We surmise that optimal interventions for patient-centered AKI care must target care components in the inpatient and outpatient settings, and across care transitions with the fundamental goals of increasing awareness of AKI, improving education and communication regarding AKI causes and self-management practices, and documentation of AKI in the medical record and in patient-facing materials. In Table 3, we outline recommendations for patient-centered AKI care best practice activities across care settings based on challenges identified in our work.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Surprisingly, 80% of AKI survivors were unaware of their condition by the time of discharge, and 21% were unaware of their AKI diagnosis at the first AKI Clinic visit. 5 , 6 The AKI survivors were also shown to be at higher risk for rehospitalization than their counterparts without AKI. A population-based study showed that 18% of AKI survivors were readmitted within the first 30 days of discharge.…”
Section: Discussionmentioning
confidence: 99%